Renewable energy consumption and business density as drivers of sustainable development - Zheng, Renzhi; Osabohien, Romanus; Madueke, Emmanuel; Jaaffar, Amar Hisham Bin (Frontiers in Energy Research, 2023)
The East Asia and Pacific region have witnessed significant economic growth in recent decades, leading to improved living standards and increased energy consumption. However, this rapid development has also resulted in environmental degradation and heightened concerns about climate change. In response, countries in the region have been increasingly focusing on sustainable development, with renewable energy consumption and business density emerging as key drivers. Given this background, this research empirically examines the impact of entrepreneurship and clean technology on sustainable development in East Asia and the Pacific region. To control for endogeneity, the study applied system the Generalized Method of Moments (SGMM) for the data sourced from the World Development Indicators (WDI) of the World Bank for the period 2015-2021. The finding indicates that both entrepreneurship and clean technology have an adverse significant impact on sustainable development in the East Asia-Pacific region. When the regions were analysed individually, the results revealed that both entrepreneurship and clean technology have a negative substantial effect on sustainable development in East Asia, but not in the Pacific region. The study concludes that entrepreneurship and renewable energy by themselves would not result in sustainable development, except some certain conditions are met. The positive impacts of entrepreneurship and renewable energy on sustainable development can only be attained when the nature, location, and practices of new businesses are low carbon in nature.